Phosphonate- and Phosphonic Acid-Functionalized Polycyclooctenes Enabling High Ionic Conductivity and Intrinsic Flame Retardancy in Solid-State Lithium-Ion Batteries - Misenan, Muhammad Syukri Mohamad; Gundogdu, Aze Ilgin; Rahim, Maheen; Figen, Aysel Kanturk; Eren, Tarik (AMER CHEMICAL SOC, 2026)
Polymer electrolytes are considered promising materials for next-generation solid-state lithium-ion batteries due to their enhanced safety, flexibility, and electrochemical stability compared to conventional liquid electrolytes. Nevertheless, major bottlenecks including low room-temperature ionic conductivity, poor electrode/electrolyte interfacial stability, and limited flame-retardant properties still hinder their practical applications. In the pursuit of safer and high-performance lithium-ion batteries (LIBs), polymer electrolytes with improved ionic conductivity, thermal stability, and flame retardancy are highly desirable. In this study, a novel phosphonate-functionalized polycyclooctene (PPCO) was synthesized and characterized as a solid polymer electrolyte for LIBs. The synthetic route began with a thiol-ene click reaction between cyclooctadiene and mercaptoethanol to afford a hydroxyl-functionalized monomer, which was subsequently reacted with a chlorophosphate reagent to introduce phosphonate groups. Polymerization using Grubbs' third-generation catalyst yielded a polymer bearing pendant phosphonate functionalities, PolyCOD(phosphonate). Phosphonic acid derivatives, PolyCOD(phosphonic acid), were further prepared via treatment with trimethylsilyl bromide. These polymers were blended with polyvinylidene difluoride (PVDF) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI). Thermal analysis confirmed successful functionalization and high thermal stability (>300 degrees C). Microcone calorimetry revealed that PolyCOD(phosphonic acid) exhibited superior heat release rate (HRR) reduction compared to PolyCOD(phosphonate). Electrochemical impedance spectroscopy demonstrated enhanced lithium-ion conductivity in the presence of LiTFSI, attributed to the strong solvation ability of the phosphonate moieties. A maximum conductivity of 0.63 & times; 10(-3) S cm(-1) at ambient temperature was achieved. The incorporation of phosphonate functionalities not only improves ionic transport but also imparts flame-retardant characteristics, establishing these materials as promising candidates for next-generation solid-state LIB electrolytes. Future work will include Li+ transference number determination, extended electrochemical stability analysis, and coin cell testing to evaluate cycling performance and interfacial stability, alongside further optimization of polymer structure for enhanced ionic conductivity.
Keywords: AUTOMOTIVE INDUSTRY; METATHESIS; ELECTROLYTES; CYCLOOCTENE; STABILITY; POLYMERS; OLEFINS; Chemistry